Down-Streaming Impact to the Competitiveness of Indonesia Cocoa - Irfan Nabhani (UIN Sunan Gunung Djati, 2024)
The objective of this paper is to provide qualitative and quantitative analysis on the competitiveness of Indonesia cocoa beans post down-streaming push by the Government of Indonesia. Indonesia cocoa has been part of the top three producers and exporters of global cocoa beans and had been shifting into cocoa processed products to create more value. Quantitative analysis from upstream perspective measures the supply concentration and competitive advantage using The Four-Firm Concentration (CR4), Herfindahl-Hirschman Index (HHI), and the model of Revealed Comparative Advantage (RCA) while value creation impacted by down-streaming is based on published data during the period of 2012-2021. The qualitative analysis uses the framework of Global Competitiveness Index to measure the competitiveness gap of Indonesia cocoa sector based on interview with Indonesia cocoa experts consisted of respected government officer, academic, researcher, cocoa trader association, and cocoa farmer association. The result concludes the domination of top four countries on supply side has shifted from â€œmoderately concentratedâ€ to â€œhighly concentratedâ€; and confirms the improvement of Indonesia cocoa from value creation perspective by down-streaming the export product. Competitiveness gap analysis compares the current condition with ideal condition of industry; as a result, identify there are one area that in line with sectoral environment and three major areas that need to be resolved to close the competitiveness gap especially in the area of productivity and efficiency, institutional framework, and prices. Government should continue the capacity building program to improve smallholdersâ€™ capability and monitor the implementation of warehouse receipt program to ensure the partiality to cocoa smallholders.